O49 Standardising simulation debrief for undergraduate interprofessional education. (31st December 2017) - Murphy, Alexandra
Abstract : Introduction and Aims: Many models of debrief have been designed for use during simulation-based education. Several of these models have been researched and the evidence elicits the advantages of implementing such tools. At the university associated with our deanery, inter-professional education training has been incorporated into the medical curriculum over the last decade. The current half day session is attended by a small group of both medical and nursing students. The students must assess and treat critically ill patients during several simulated scenarios. The sessions are facilitated by a nurse educator and a clinical teaching tutor. The roles of the clinical teaching tutors are fulfilled by senior anaesthetic registrars. As one of the six current clinical teaching tutors, I identified that there was marked variation in the level of training we each had received on delivering simulation-based education. This translated to each of us facilitating the debrief in a range of styles, including the use of an assortment of evidence-based debrief models. Description: The unique features of simulation-based education in this setting included the multidisciplinary nature of the participants and also their relative unfamiliarity with this method of learning. It is well established that debriefing is the section of simulation-based education that offers most opportunity for learning and, therefore, it should be prioritised for optimisation and standardisation. I chose one model of debriefing, adapted it for use in this setting and introduced it to the other clinical teaching tutors. In order to assess if a standardised debrief model would benefit the students, I designed a survey that was anonymously completed by the students and rated various aspects of their experiences. The survey was completed by 62 students who attended sessions prior to the introduction of the new debrief model. The same survey was then completed by 49 students who participated in sessions following institution of the standardised approach. Discussion: The results demonstrated an improvement across all assessed elements of the students' experiences, including greater confidence in their role as both participant and observer during the scenarios. The students also felt that their clinical knowledge and skills and inter-professional skills were greater enhanced with the use of the standardised debrief model. There are currently plans in place to facilitate the wider use of this debrief model with the aim of standardising simulation-based education throughout our region.